Phenomenon of legal culture of kazakhstan society - Akhmetov, A.S. (KSU Publ., 2018)
This article is devoted to the analysis of the legal culture of civil society. The purpose of the article is to highlight the value orientations of the legal culture of the Republic of Kazakhstan in the process of developing a democratic state. The essence and structure of legal culture and its features are considered in the article. The author pays special attention to the study of the value aspects of the legal culture of the Republic of Kazakhstan in the development of a democratic state and the formation of a civil society. The author concludes that the main factors are the formation of an anti-corruption culture of anti-corruption education and training, and great importance is increasing the level of legal culture of the individual. In addition, the main approaches to understanding legal culture have been studied. The scientific work is written on the basis of scientific research of Kazakhstan and foreign authors on the nature of law, legal culture, its values in the formation of civil society and the rule of law in the Republic of Kazakhstan. It concludes that the main principle of civil society advocates free and comprehensive development of the individual in society, and that civil society starts with the appearance of the citizen as a free member of society who is aware of its purpose, endowed with a set of rights and freedom and the duty of responsibility for their actions to the society.
Қазақстандық қоғамның құқықтық мəдениет феномені
Феномен правовой культуры казахстанского общества
Keywords: law; culture; identity; legal culture; a democratic state and its values; civil society; legal education; legal upbringing